Cognitive abnormalities in Becker muscular dystrophy: a mysterious link between dystrophin deficiency and executive functions - Pezzoni, Laura; Brusa, Roberta; Difonzo, Teresa; Magri, Francesca; Velardo, Daniele; Corti, Stefania; Comi, Giacomo Pietro; Saetti, Maria Cristina (Neurological sciences, 2024)
Background Distrophinopathies are a heterogeneous group of neuromuscular disorders due to mutations in the DMD gene. Different isoforms of dystrophin are also expressed in the cerebral cortex and Purkinje cells. Despite cognitive abnormalities in Duchenne muscular dystrophy subjects that have been described in the literature, little is known about a comprehensive cognitive profile in Becker muscular dystrophy patients. Aim The aim of this study was to assess cognitive functioning in Becker muscular dystrophy patients by using an extensive neuropsychological battery. Our hypothesis is that the most impaired functions are the highly intentional and conscious ones, such as working memory functions, which require a prolonged state of cellular activation. Methods We performed an extensive neuropsychological assessment on 28 Becker muscular dystrophy patients from 18 to 65 years old. As control subjects, we selected 20 patients with limb-girdle muscular dystrophy, whose clinical picture was similar except for cognitive integrity. The evaluation, although extended to all areas, was focused on prefrontal control skills, with a distinction between inhibitory processes of selective attention and activating processes of working memory. Results and conclusions Significant underperformances were found exclusively in the Dual Task and PASAT tests, to demonstrate a selective impairment of working memory that, while not causing intellectual disability, reduces the intellectual potential of patients with Becker muscular dystrophy.